Consumer Sentiment as a Segmentation Criterion for Individual Customers using Internet Banking Services - Kaczmarek, Mirosława (Studia Oeconomica Posnaniensia, 2015)
The aim of this paper is to identify the relationships between the behaviour of consumers using online banking services and the level of consumer sentiment. Based on the results of a study conducted in the Wielkopolska region using individual interviews with customers who use online banking services, three customer segments were identified which differed from one another regarding the value of the consumer confidence index. The three groups comprised optimists, pessimists and neutral customers. Analyses show that the customer segments identified differ with respect to the frequency of using bank websites, as well as performing various banking transactions such as doing bank transfers or checking account balance and history. In addition, age has been found to be the socio-demographic characteristic which most clearly differentiates the three customer segments.